CONCEPTUAL MODEL OF STUDENTS ABROAD’S BEHAVIOUR: AGENT-BASED MODELING APPROACH - Inayati, Tutik; Putro, Utomo Sarjono; Novani, Santi; Nurdayat, Ilham Fadhil (UI Scholars Hub, 2021)
Manuscript type: Original Papers Research Aims: To explore the behavioral process of international students on how they can change their decision to remain or return home based on their interactions with other agents during their studies. Design/methodology/approach: This paper uses an agent-based methodology approach to simulate the behavior of students based on their interactions while studying abroad. A combination of four parameters with three different scenarios and 40 repetitions in every scenario are conducted to verify the model; 81 simulations are determined to simulate this model. Research Findings: The number of natives interacting with students is proven as one single important parameter that influences the number of remaining students and their probability density. Theoretical Contribution/Originality: Utilisation of agent-based simulation to predict behavior of students Practitioner/Policy Implication: Supporting good quality of life condition for students environmentally and socially Research limitation/Implications: Interaction with fellow students, natives, recruiters abroad and in home country are the only interactions considered in this model. More elaborate and complicated model is needed.